A learner corpus study of the article system / Siti Fatimah Yusof - Siti Fatimah , Yusof (2020)
Studies on learner language tend to compare learners’ second language with a target language. Informed by recent reconceptualization of language learning in which bilingual minds are viewed as fundamentally different from monolingual minds (see, e.g., the notion of multicompetence by Cook, 1991, 2013), the present study explores how learner language is studied as a separate and independent linguistic system. By using Antconc 3.4.4w, this study analysed a recently developed learner corpus of written data by a group of secondary school students in Malaysia, examining how language development takes place over time. Participants composed essays based on a picture prompt and changes in their language use through the study of the articles (a, an and the) were tracked over time. Findings suggest that there were changes in the way the students used language as evidenced in their texts, from the frequency of use, the distribution of patterns as well as senses.